The alcohol industry, the tobacco industry, and excise taxes in the US 1986-89: new insights from the tobacco documents - Matthew Lesch; Jim McCambridge (BMC, 2022)
Abstract Background The UCSF Industry Documents Library has provided public health researchers with key insights into the organization of political activities in the tobacco industry. Much less is known about the alcohol industry. In the US, there is some existing evidence of cooperation between the two industries, particularly in areas where there are mutual interests and/or policy goals at stake. Efforts to raise excise taxes on tobacco and alcohol products are one such example. Methods We systematically searched the UCSF Industry Documents Library for data on alcohol industry actors and their political activities. Using content generated by alcohol and tobacco actors, we sought to identify new evidence of collaborations to shape excise tax policy debates in the US in the 1980s and 1990s. Results We uncover evidence of the alcohol industry's efforts to shape excise tax policy debates, both at the national and state level. Excise taxes were defined by both alcohol and tobacco companies and related organisations as a key threat to profits. We show how the alcohol industry confronted this challenge in the late 1980s in the US, uncovering the range of monitoring, coordinating, and public-facing activities used to defeat proposed tax increases at both state and federal levels. The former draws particular attention to Oregon, where alcohol industry actors were not simply operating at the behest of the tobacco industry, but actively led a campaign to advance both brewing and tobacco interests. Conclusions The tobacco documents offer a key resource for studying economic interests beyond that of the tobacco industry, operating in collaboration with tobacco companies. Here, brewers advanced shared interests with tobacco, and these findings have implications for advancing understanding of alcohol and tobacco industry political strategies. The findings also suggest that financial documents from other public repositories could be used to generate new inferences about corporate political activities.